2020
DOI: 10.7759/cureus.9217
|View full text |Cite
|
Sign up to set email alerts
|

Utilizing Closed Incisional Negative Pressure Therapy Reduces Peripheral Bypass Infection Rates Without Increasing Costs

Abstract: Introduction: We evaluated outcomes of closed incisional negative pressure therapy (ciNPT) on surgical site infection (SSI) rates in lower extremity bypass patients. We sought to determine whether or not the routine use of ciNPT is a cost-effective measure. Methods: During a period from May 2018 to August 2018, our institution transitioned to the routine use of ciNPT for re-vascularization procedures. We retrospectively reviewed our outcomes before and after the initiation of ciNPT. Group A included… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 10 publications
0
3
0
1
Order By: Relevance
“…The included studies represent a global surgical patient population with 7451 patients receiving ciNPT and 16,085 patients receiving SOC across 16 countries. 11–16,20–97 The countries represented included the USA (n = 42), Germany (n = 11), Australia (n = 6), Canada (n = 5), Italy (n = 4), Spain (n = 3), the UK (n = 3), Denmark (n = 2), and one each from Austria, Brazil, France, Ireland, the Netherlands, South Africa, Taiwan, and Turkey. Dressings used in the SOC population varied and included gauze dressings, antimicrobial hydrofiber dressings, absorbent dressings, hydrocolloid dressings, occlusive dressings, or foam dressings.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The included studies represent a global surgical patient population with 7451 patients receiving ciNPT and 16,085 patients receiving SOC across 16 countries. 11–16,20–97 The countries represented included the USA (n = 42), Germany (n = 11), Australia (n = 6), Canada (n = 5), Italy (n = 4), Spain (n = 3), the UK (n = 3), Denmark (n = 2), and one each from Austria, Brazil, France, Ireland, the Netherlands, South Africa, Taiwan, and Turkey. Dressings used in the SOC population varied and included gauze dressings, antimicrobial hydrofiber dressings, absorbent dressings, hydrocolloid dressings, occlusive dressings, or foam dressings.…”
Section: Resultsmentioning
confidence: 99%
“…The 84 studies identified encompassed cardiac surgery (n = 8), general abdominal surgery (n = 21), obstetric and gynecologic surgery (n = 8), orthopedic surgery (n = 16), plastic surgery (n = 16), and vascular surgery (n = 15). 11–16,20–97…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Dabei erzielten die analysierten RCTs eine signifikante Reduktion der postoperativen Wundinfektionsrate um 5 bis 8 Prozentpunkte und die Metaanalyse von Saunders et al identifizierte eine "Number needed to treat" von 20 [4,34]. Spezifisch für gefäßchirurgische Zugangswege und Operationen konnten aktuelle Studien und Metaanalysen mit signifikanter Reduktion der postoperativen Wundinfektionsrate für Leistenzugänge [5,18], periphere Bypasschirurgie [13], Majoramputationen [6] und generell vaskuläre Chirurgie [35,42] aus den letzten drei Jahren identifiziert werden. Hinsichtlich weiterer postoperativer Wundkomplikationen (z.…”
Section: Wundeunclassified